AGAINST GENDER DISCRIMINATION IN ANGELA ROBINSON'S HERBIE FULLY LOADED (2005) MOVIE: A FEMINIST APPROACH - INDARTI , DWI (2010)
This study is aimed to show the against gender discrimination in Herbie Fully Loaded movie by using feminist approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the feminist approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Herbie Fully Loaded movie directed by Angela Robinson released in 2005. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en-scene, cinematography, sound, and editing are related to each other and form unity to be good quality of a movie. Second, based on the feminist analysis, Angela Robinson represents the form of gender discrimination. The character of Maggie struggle for quality in position, role, right and participation than man.